2012
DOI: 10.5194/cpd-8-2187-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alluvial fan dynamics in the El'gygytgyn Crater: implications for the 3.6 Ma old sediment archive

Abstract: A sedimentological program has been conducted using frozen core samples from the 141.5 m long El'gygytgyn 5011-3 permafrost well. The drill site is located in sedimentary permafrost west of the lake that partly fills the El'gygytgyn Crater. The total core sequence is interpreted as strata building up a progradational alluvial fan delta. Four structurally and texturally distinct sedimentary units are identified. Unit 1 (141.5–117.0 m) is comprised of ice-cemented, matrix-supported sandy gravel and intercalated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…However, these can largely be excluded due to several reasons: on the one hand thermal properties have been determined by different approaches (indirect as well as measurements), on the other hand permafrost has been present for at least some ten thousand years. The warmer period during the Allerød (13.3-13.1 kyr BP), when the lake level was some 5 m higher than modern levels and flooded the coring site at that time (Schwamborn et al, 2008(Schwamborn et al, , 2012, was studied by different model runs and showed that there is no influence on the current temperature field anymore.…”
Section: Transient Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these can largely be excluded due to several reasons: on the one hand thermal properties have been determined by different approaches (indirect as well as measurements), on the other hand permafrost has been present for at least some ten thousand years. The warmer period during the Allerød (13.3-13.1 kyr BP), when the lake level was some 5 m higher than modern levels and flooded the coring site at that time (Schwamborn et al, 2008(Schwamborn et al, , 2012, was studied by different model runs and showed that there is no influence on the current temperature field anymore.…”
Section: Transient Simulationsmentioning
confidence: 99%
“…Regarding the thermal properties of the prevailing sediments and rocks in frozen condition, we performed thermal conductivity measurements on one core sample retrieved from borehole (2) This sample consists of sandy gravel, and is representative for much of the material from the permafrost core (Schwamborn et al, 2012) associated with the model's unit 2 in Fig. 2.…”
Section: Available Datamentioning
confidence: 99%
“…This sample consists of sandy gravel, and is representative for much of the material from the permafrost core (Schwamborn et al, 2012) associated with the model's unit 2 in Fig. 2.…”
Section: Available Datamentioning
confidence: 99%